2009
DOI: 10.1088/1748-0221/4/06/p06005
|View full text |Cite
|
Sign up to set email alerts
|

A FEM simulation study of the optimization of the imaging attributes of a microwave radiometry system with possible functional imaging capabilities

Abstract: Microwave radiometry is a measurement technique which detects natural-thermal radiation emitted by matter. The human brain having certain temperature and specific electromagnetic properties emits chaotic radiation throughout the whole electromagnetic spectrum. A novel Microwave Radiometry Imaging System (MiRaIS) comprising an ellipsoidal conductive wall cavity and sensitive radiometric receivers, operating at low microwave frequencies (1-4GHz), has been used the past four years in various experiments to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0
1

Year Published

2009
2009
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
4
3
0
1
Order By: Relevance
“…Previous simulation results indicated a 30-40% increase in the electric field values and energy absorption inside the head model [31,32]. The experimental results presented in this paper indicate indeed an increase of about 30-50% in all frequencies when the dielectric layer of ε r = 6 is present.…”
Section: Microwave Radiometry Experimentssupporting
confidence: 62%
See 1 more Smart Citation
“…Previous simulation results indicated a 30-40% increase in the electric field values and energy absorption inside the head model [31,32]. The experimental results presented in this paper indicate indeed an increase of about 30-50% in all frequencies when the dielectric layer of ε r = 6 is present.…”
Section: Microwave Radiometry Experimentssupporting
confidence: 62%
“…The scope of the present research focuses mainly on the experimental use of dielectric matching materials to improve the system focusing properties, in terms of detection/penetration depth and spatial resolution, during radiometric monitoring and hyperthermia experiments with phantoms, verifying at the same time previous theoretical results [30][31][32].…”
Section: Introductionsupporting
confidence: 63%
“…In an effort to overcome these issues, extensive electromagnetic analysis has been performed using various simulation setups, including low loss dielectric materials as filling inside the entire ellipsoidal volume [Karanasiou et al, 2008; Gouzouasis et al, 2009b; Karathanasis et al, 2009b] or as matching layers in conjunction with left‐handed materials (metamaterials) [Karathanasis et al, 2007a; Karanasiou et al, 2008]. The results elicited from these studies showed that in both cases a stepped refraction index on the head–air boundary is achieved, resulting in reduced reflection of the electromagnetic waves and, consequently, an increase of the system's sensing capability and detection depth.…”
Section: Methodsmentioning
confidence: 99%
“…The results elicited from these studies showed that in both cases a stepped refraction index on the head–air boundary is achieved, resulting in reduced reflection of the electromagnetic waves and, consequently, an increase of the system's sensing capability and detection depth. Also, in the first case, improvement of the spatial sensitivity in relative movements of the subject around the focal point was observed [Karanasiou et al, 2008; Karathanasis et al, 2009b].…”
Section: Methodsmentioning
confidence: 99%
“…Σύμφωνα με προηγούμενες θεωρητικές αναλύσεις η τομή δεν επηρεάζει τις ιδιότητες εστίασης του συστήματος [140]- [144].…”
Section: η αγώγιμη ελλειψοειδής κοιλότηταunclassified